Pengaruh Pandemi Covid-19 Terhadap Jumlah Sampah di Tempat Pemrosesan Akhir Regional Kota Payakumbuh - Yenni Ruslinda; Indah Kurnia Asyura; Rizki Aziz (Jurnal Serambi Engineering, 2021)
Restrictions on community activities during the Covid-19 pandemic have an impact on the amount of waste a city produces. This study aims to analyze the amount of incoming waste at the Payakumbuh Regional Final Processing Site (TPA) before and during the Covid-19 pandemic, analyze the impact of the pandemic on waste sources and provide recommendations for waste management during the pandemic. Data on the amount of waste entering the TPA was obtained from measurements of waste at the weighbridge before the pandemic (February – March 2020) and during the pandemic (April – May 2020). The analysis of the impact of the pandemic on the source of the waste is based on the results of interviews with truck drivers and analysis of truck routes. The results showed a decrease in the amount of waste transported to the landfill by 11.15% during the Covid-19 pandemic. The average amount of waste before the pandemic was 237.36 tons/day, while during the pandemic is 210.90 tons/day. The decrease in the amount of waste is due to restrictions on community activities outside the home with the implementation of the Large-Scale Social Restriction (PSBB) policy. The implementation of PSBB policy during the pandemic caused a decrease in the amount of waste from institutional, commercial and city service facilities by 29.48-50% and an increase in domestic sources by 21.22%.